Fitrah and Character Formation of Generation Z in the Society 5.0 Era - Layinah, Leni; Kosasih, Aceng; Tohari, Heri Mohamad (Atthulab: Islamic Religion Teaching and Learning Journal, 2025)
This study examines the role of the concept of fitrah in the formation of Generation Z character in the era of Society 5.0 which is characterized by the integration of digital technology and social life. The focus of the research is directed at the strategy of internalizing the values of religiosity, morality, and social responsibility in character education that is adaptive to technological developments. The methods used are qualitative-based literature through systematic literature review of national and international articles, analysis of classical Islamic texts, education policies, and empirical findings on the digital behavior of Generation Z. The results show three main challenges of Generation Z, namely digital overexposure, weakening of face-to-face social interaction, and value identity crisis. Fitrah-based education contributes to strengthening faith, morals, digital ethics, and social awareness by emphasizing a harmonious relationship with God, fellow humans, and nature. Thus, fitrah has the potential to become a strategic foundation for the development of a holistic character education model that is relevant to the vision of Society 5.0, where education policy needs to integrate the potential of fitrah with academic achievement and the formation of noble morals.